D(i)e verhouding prediking, mus(z)iek en liturgie - Wepener, Cas; Klomp, Mirella (Hervormde teologiese studies, 2015)
The relationship between preaching, music and liturgy. In the Reformed liturgy in South Africa the sermon has traditionally been reserved a special place, taking precedence over the liturgy and music. In this article an argument is put forward for a better balance between preaching, liturgy and music in the Reformed liturgy in churches in South Africa. In order to do so, the South African Reformed liturgical context is briefly sketched and thereafter a theological and liturgical-historical argument is presented. Existing approaches with regard to the relationship between liturgy, music and preaching by some established scholars are discussed before the implications of the argument are examined in conclusion.